Neurobehavioral Evaluation of Renin-Angiotensin System Modulators in an MPTP-Induced Model of Parkinson’s Disease in Swiss Albino Mice - K.G. Prakash; K. Saniya; Shubham Jaju; Madhavrao Chavan; K. Mythili Bai; Aishwarya Mantri (Annals of African Medicine, 2026)
Abstract Background: Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor and nonmotor deficits. Emerging evidence suggests a role of the renin-angiotensin system (RAS) in neurodegeneration, making it a potential therapeutic target. Aim: To evaluate the neuroprotective effects of RAS-modulating drugs such as captopril, perindopril, and losartan in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced model of PD. Methods: An experimental in vivo study was conducted using Swiss albino mice ( n = 6 per group). Parkinsonism was induced using MPTP (25 mg/kg). Animals were divided into six groups: vehicle control, negative control, standard control (levodopa + benserazide), and three treatment groups receiving captopril (20 mg/kg), perindopril (5 mg/kg), and losartan (90 mg/kg). Behavioral assessments included actophotometer, rotarod, grip strength, hole board, tail suspension, forced swim, and elevated plus maze tests. Data were expressed as mean ± standard deviation and analyzed using analysis of variance. Results: MPTP significantly impaired motor and behavioral parameters, as evidenced by reduced locomotor activity (21.17 ± 2.70 vs. 286.50 ± 8.77), decreased rotarod performance, and increased immobility time in depression models. Treatment with RAS modulators significantly improved these parameters ( P < 0.05). Losartan (274.67 ± 11.15) and captopril (267.33 ± 16.01) showed greater improvement in locomotor activity compared to perindopril. Similarly, all treatments reduced immobility time and improved anxiety-related behavior in the elevated plus maze. Conclusion: RAS modulators demonstrated significant neurobehavioral protection in MPTP-induced Parkinsonism, suggesting their potential as adjunct therapeutic agents in PD.